An Objective Assessment Tool (gOAT) of helicopter pilot's performance - Kopyt, A.; Bibik, P.; Świętoń, G. (My University, 2018)
In this research an Objective Assessment Tool (gOAT) is presented. The main idea of the system is to develop a tool that provides more detailed information about the pilots' performance. The gOAT system bases on the Mission Task Elements (MTEs) taken from the Aeronautical Design Standard Performance Specification Handling Qualities Requirements for Military Rotorcraft (ADS-33), and use the data recorded by the flight simulator software. In the ADS-33 document the criteria for tasks are limited and not very complex. The gOAT systems goal is to enlarge the task criteria, so the feedback delivered by the system is wider. That would automatically provide more information and data for postprocessing and evaluation. During simulated flight the gOAT system not only provides an error/deviation compared to the desired pattern, but also has an 'assistant' functionality. The developed system could be used as a tool to improve the current flight skills and performance by giving the cues and tips for pilot. The modular architecture of the system allows to implement additional indicators for the pilot, so the task is done with higher precision